A leitura e seu valor social: um estudo sobre as práticas de leitura e condições socioeconômicas e culturais - Dall Agnol, Samira (My University, 2014)
Aiming to notice the relations between the reading practices and the social, economic and cultural conditions of Nova Bassano, firstly, data were collected, through a questionnaire, from students and teachers of Colbachini School and, after that, some statements from people of the community were collected, through the hearsay technique. The results point that, while in the school community there is certain effervescence of reading, through book-promoting markets, lectures with writers, reading indications, etc., in the community in general, the reading loses power, for the reason that it cannot find neither resonance nor prestige. It can be thought that, in the bassanense community, the reading act does not constitute a cultural trace and one of the reasons could be related to the formation of the RCI-RS and, as a consequence, to the formation of the city. However, it is perceptible the efforts made from the school, mainly from the teachers, in an attempt of modifying this situation. The data of Ensino Fundamental students show that, if instigated and stimulated, the new generations could institute prestige to cultural practices not yet enough valued nowadays to this community, as reading practices.
Com o intuito de perceber as relações entre as práticas de leitura e as condições socioeconômicas e culturais de Nova Bassano, foram coletados, primeiramente, dados de alunos e professores do Colégio Colbachini, através de questionário, e, em seguida, foram compilados depoimentos da comunidade em geral, através da técnica de oitiva. Os resultados apontam que, enquanto na comunidade escolar ocorre certa efervescência da leitura, através de feiras do livro, palestras com escritores, indicação de leituras, etc., na comunidade em geral, a leitura perde forças, não encontrado nem ressonância, nem prestígio. Pode-se pensar que, na comunidade bassanense, a leitura não constitui um traço cultural e um dos motivos pode estar vinculado à questão da formação da RCI-RS e, por conseqüência, do município. Entretanto, é perceptível o esforço da comunidade escolar, principalmente dos professores, na tentativa de modificar essa situação. Os dados dos alunos do Ensino Fundamental indicam que, se instigadas e estimuladas, as novas gerações podem instituir prestígio a práticas culturais ainda pouco valorizadas nessa comunidade, como as práticas de leitura.
Keywords: Letras; Práticas de leitura; Condições socioeconômicas e culturais; Valor social da leitura; Reading practices; Social, economic and cultural conditions; Social value of reading